Whole-genome analysis of Mannheimia haemolytica serotype A2 to identify potential vaccine candidates against acute pneumonia in alpacas - Juscamayta L., Eduardo (2017)
The aim of this study was to identify immunoprotective antigens in the genomic sequence of Mannheimia haemolytica serotype A2 isolated from sheep and available in databases that can be used as potential vaccine candidates against pneumonia in alpacas. To do this, the complete genome sequence of this organism available in databases was used and by using bioinformatics tools was proceeded to search for and identification of candidate genes, functional annotation, predicting the subcellular localization and identification of sequence motifs including transmembrane domains, secretion signal peptides and lipoproteins. Virulence factors were identified in the database of virulence factors (VFDB) and the microbial database of virulence factors (MvirDB). Selection criteria included conserved proteins, secreted and associated surface with transmembrane helices <1. Homology search of genes was performed with the database of protective antigens (Protegen), allowing the identification of 23 potentially immunoprotective antigens conserved between virulent M. haemolytica serotypes and other pathogens of the family Pasteurellaceae. The genes identified are related to the pathogenesis, virulence and immune system evasion of the host and they could be great candidates to be evaluated as potential vaccines against pneumonic pasteurellosis.